Evaluation of Elafin as a Prognostic Biomarker in Acute Graft-versus-Host Disease: M. G. Zewde et al - Zewde, Makda Getachew; Morales, George; Gandhi, Isha; Özbek, Umut; Aguayo-Hiraldo, Paibel; Ayuk, Francis; Baez, Janna; Chanswangphuwana, Chantiya; Choe, Hannah; DeFilipp, Zachariah; Etra, Aaron; Grupp, Stephan; et al. (Transplantation and Cellular Therapy, 2021)
Acute graft-versus-host disease (GVHD) is a major cause of mortality in patients undergoing hematopoietic cell transplantation (HCT) for hematologic malignancies. The skin is the most commonly involved organ in GVHD. Elafin, a protease inhibitor overexpressed in inflamed epidermis, was previously identified as a diagnostic biomarker of skin GVHD; however, this finding was restricted to a subset of patients with isolated skin GVHD. The main driver of nonrelapse mortality (NRM) in HCT recipients is gastrointestinal (GI) GVHD. Two biomarkers, Regenerating islet-derived 3a (REG3α) and Suppressor of tumorigenesis 2 (ST2), have been validated as biomarkers of GI GVHD that predict long-term outcomes in patients treated for GVHD. We undertook this study to determine the utility of elafin as a prognostic biomarker in the general population of acute GVHD patients in whom GVHD may develop in multiple organs. We analyzed serum elafin concentrations as a predictive biomarker of acute GVHD outcomes and compared it with ST2 and REG3α in a large group of patients treated at multiple centers. A total of 526 patients from the Mount Sinai Acute GVHD International Consortium (MAGIC) who had received corticosteroid treatment for skin GVHD and who had not been previously studied were analyzed. Serum concentrations of elafin, ST2, and REG3α were measured by ELISA in all patients. The patients were divided at random into equal training and validation sets, and a competing-risk regression model was developed to model 6-month NRM using elafin concentration in the training set. Additional models were developed using concentrations of ST2 and REG3α or the combination of all 3 biomarkers as predictors. Receiver operating characteristic (ROC) curves were constructed using the validation set to evaluate the predictive accuracy of each model and to stratify patients into high- and low-risk biomarker groups. The cumulative incidence of 6-month NRM, overall survival (OS), and 4-week treatment response were compared between the risk groups. Unexpectedly, patients in the low-risk elafin group demonstrated a higher incidence of 6-month NRM, although the difference was not statistically significant (17% versus 11%; P = .19). OS at 6 months (68% versus 68%; P > .99) and 4-week response (78% versus 78%; P = .98) were similar in the low-risk and high-risk elafin groups. The area under the ROC curve (AUC) was 0.55 for elafin and 0.75 for the combination of ST2 and REG3α. The addition of elafin to the other 2 biomarkers did not improve the AUC. Our data indicate that serum elafin concentrations measured at the initiation of systemic treatment for acute GVHD did not predict 6-month NRM, OS, or treatment response in a multicenter population of patients treated systemically for acute GVHD. As seen in previous studies, serum concentrations of the GI GVHD biomarkers ST2 and REG3α were significant predictors of NRM, and the addition of elafin levels did not improve their accuracy. These results underscore the importance of GI disease in driving NRM in patients who develop acute GVHD.
CRIS-Team Scopus Importer:2021-12-17
Keywords: biomarkers; Graft-versus-host disease; hematopoietic cell transplantation